Determinants of firm Profitability in Nigeria: Evidence from dynamic panel models - Ibrahim Abidemi Odusanya; Olumuyiwa Ganiyu Yinusa; Bamidele M. Ilo (SPOUDAI - Journal of Economics and Business, 2018)
This study examines the determinants of firm profitability for 114 firms listed on the Nigerian Stock Exchange (NSE) from 1998 to 2012, using the system Generalized Method of Moments (GMM). The results show that lagged profitability exerts significant positive effect on contemporaneous firm profitability. However, short-term leverage, inflation rate, interest rate and financial risk have significant negative effects on firm profitability. The study therefore suggests, among other recommendations, that the cost of borrowing to the real sector of the economy should be reduced in order to minimize costs of production, enhance productivity and profitability while necessary macroeconomic policies should be put in place by the government to curb inflationary pressure in the economy.
Keywords: B21; C23; L25; 330; Firm; Non-financial; Profitability; Leverage; Generalized Method of Moments; Nigeria